Modeling The Impact Analysis of The Covid-19 Pandemic On The Tourism Sector In Palopo City With A Nonparametric Regression Approach - Denysia, Denysia; Hidayat, Rahmat (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The implementation of social distancing causes a huge effect on the life sector in Indonesia, one of which is the tourism sector which has experienced the greatest impact due to this policy. One of the treatments that can be done is to find out the factors that are thought to have an influence on the increase in the tourism sector in Palopo city, many methods can be done, one of which is the regression analysis method. This study uses Spline non-parametric regression in modeling the data. The non-parametric regression model was chosen based on results of the identification that the data does not follow a certain distribution pattern. Gross regional domestic product data is used in the model. This can be seen from the resulting  value of 76.94%. Gross Regional Domestic Product data is also modeled using multiple linear regression. This modeling is intended as a comparison model. The results show that the use of the non-parametric Spline better model in modeling the data compared to multiple linear regression.